QUO VADIS AKUISISI TOKOPEDIA OLEH GOJEK DI ERA EKONOMI DIGITAL? Quo Vadis Tokopedia Acquisition by Gojek in the Digital Economy Era? - Sabirin, Ahmad; Anggraini, Anna Maria Tri (Faculty of Law, Universitas Trisakti, 2024)
From early 2021 to 2022, Acquisitions and Mergers are an interesting issue to discuss. Two large companies, namely PT Karya Anak Bangsa, made acquisitions of PT Tokopedia. KPPU, as the supervisory body for business competition, assessed the acquisitions of the two companies, whether or not the acquisitions made by a business violated business competition in Indonesia. If we look at the provisions of Law No. 5 Year 1999 which provides three indicators to declare the existence of unfair business competition, namely; 1) Business competition conducted dishonestly; 2) Business competition is conducted in an unlawful manner. 3) Business competition conducted by inhibiting competition among business actors. These indicators have their own challenges in the era of digital economy as today, there are many challenges in enforcing business competition. Merger assessment using the SLC test method is insufficient to apply because the SLC test focuses less on market structure issues, and only focuses on the competitive impact of the acquisition and the market power that emerges after the acquisition. That is, the SLC test looks at the likelihood that prices will rise after an acquisition occurs. While the determination of relevant market and market share is very important in assessing the effect on competition, this has been done by the European Union, so the assessment of acquisitions for large technology companies needs to be evaluated.